2015
DOI: 10.1021/acs.jmedchem.5b01542
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolo[3,4-c]pyridine-1,3(2H)-diones: A Novel Antimycobacterial Class Targeting Mycobacterial Respiration

Abstract: High-throughput screening of a library of small polar molecules against Mycobacterium tuberculosis led to the identification of a phthalimide-containing ester hit compound (1), which was optimized for metabolic stability by replacing the ester moiety with a methyl oxadiazole bioisostere. A route utilizing polymer-supported reagents was designed and executed to explore structure-activity relationships with respect to the N-benzyl substituent, leading to compounds with nanomolar activity. The frontrunner compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 30 publications
0
69
0
1
Order By: Relevance
“…Hitherto, high-throughput screening efforts have mainly yielded classes of small-molecule inhibitors active on either ATP synthase (8, 26) or the cytochrome bc 1 complex (23, 25, 26). The reasons for this preference are obscure but may be related to the central role of these two enzymes in either establishing or utilizing the proton motive force.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hitherto, high-throughput screening efforts have mainly yielded classes of small-molecule inhibitors active on either ATP synthase (8, 26) or the cytochrome bc 1 complex (23, 25, 26). The reasons for this preference are obscure but may be related to the central role of these two enzymes in either establishing or utilizing the proton motive force.…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome bd is important for growth under low oxygen tensions as well as for survival in the mammalian host (3436). Upon mutation or chemical inhibition of the cytochrome bc 1 complex, several M. tuberculosis strains are able reroute respiratory electron flux to cytochrome bd (24, 37, 38), leading to decreased sensitivity for cytochrome bc 1 inhibitors (24, 25). Cytochrome bd can also protect mycobacteria against bedaquiline (3942) and clofazimine (41).…”
Section: Introductionmentioning
confidence: 99%
“…The first of these limitations can be ameliorated through the use of different screening conditions (6)(7)(8), whereas counterscreening strategies can eliminate known (and promiscuous) targets (9,10). In contrast, establishing the MOA usually depends on the ability to raise-and then genotype-mutant bacteria with heritable resistance to the applied agent (11).…”
mentioning
confidence: 99%
“…The mycobacterial respiratory cytochrome bc1 complex was identified as the target for these compounds. Nevertheless, mouse pharmacokinetics studies showed high clearance and low plasma exposure for compound ( 28 ) [50]. In another study, a series of twenty-seven benzo[ d ]oxazol-2(3 H )-one derivatives were synthesized.…”
Section: Antituberculosis Compoundsmentioning
confidence: 99%